Analyzing The Impact of Productive Zakat Utilization on The Mustahiq Economic Independence in Malaysia and Indonesia - Rifuddin, Burhan; Rismayanti, Rismayanti; Mas, Nur Amal; Kartika, Betania (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to determine the institutional system of zakat management, the distribution mechanism of productive zakat, the influence of the utilization of productive zakat, and the impact of productive zakat empowerment on mustahiq economic independence in Malaysia and Indonesia. This research is a qualitative and quantitative research (mixed-method). The instrument of data collection was observation, literature study interviews and questionnaires which were tested with validity and reliability tests. Multiple regressions and descriptive analysis were employed as analytical tools. The focus of this study is on the development of business capital and human resources. The findings reveal that the current zakat institutional system in Malaysia and Indonesia may be compared on a number of levels, including legal basis, management institutions, management efforts, collection and distribution, and the nature and aspects of consequences. Economic independence of the mustahiq can be influenced in a variety of ways. Firstly, productive zakat has a 49.9% effect in Malaysia and 45.7 percent in Indonesia. Next, the provision of venture capital has a partially negative and inconsequential effect in Malaysia, with a -12.8 percent effect. Meanwhile, in Indonesia, business capital has a 50.0 percent positive and substantial influence. Human resource development has also had a good and considerable impact in Malaysia (76.5%) and Indonesia (31.6%). Finally, the impact of productive zakat usage in general has a considerable impact, as evidenced by interviews with informants who stated that productive zakat had an impact on mustahiq economy independence, as measured by the ratio of mustahiq to muzakki, which is about 50:50.